Avaliação de risco de corrupção: a percepção de coordenadores das Redes Estaduais de Controle da Corrupção - Santos, Jose Janaildo dos (2019)
This research analyzes the perception of the State Corruption Control Network (RECC) Coordinators' perception of factors that facilitate or hinder the adoption of a corruption risk assessment (ARC) approach in planning their actions. This is a qualitative and exploratory research based on the Grounded Theory methodology. Data collection was performed through semi-structured interviews with RECC Coordinators, and triangulated with the opinions of other anti-corruption experts. Data processing and analysis were performed with the support of the MAXQDA 2018 qualitative analysis software. As a result, 121 codes and their concepts were identified, related to facilitating, limiting and technical requirements for the adoption of an ARC action in the planning. RECC. In axial coding, such codes have been collapsed into the following categories: "Information, Actors, Process, Product, and Trust in the Network Environment." The “Trust” category has emerged as the central category for RECC actions and the functioning of these Networks. As for an ARC approach, compatible with the actions developed in the RECC, the result presented by the “Product” category indicates that a “cascade” approach involving more than one ARC approach or typology would be more appropriate. However, the category “Actors” points to the lack of qualification of the staff and the need for training in order to develop the technical skills necessary to carry out Corruption Risk Assessment actions in the Control Networks.